Value, Size, and Momentum across Countries - Zaremba, Adam; Konieczka, Przemyslaw (Indian Journal of Finance, 2014)
The study investigated the characteristics of inter-country value, size, and momentum premiums. We have contributed to the asset-pricing literature in three ways. First, we have provided fresh evidence for value, size, and momentum premiums in country returns. Second, we showed that these premiums are robust to the changes of functional currencies or countries' representative indices. Third, we demonstrated that the country-level value, size, and momentum premiums tend to strengthen each other in double-sorted portfolios. We examined listings of stocks in 66 countries between the time period from 2000 and 2013.